(untitled) (Fiep Bulletin - online, 2014)
The present paper aims the proposition of a reflection on the processes of constitution of body subjectivities in the current days. For such, adopts the philosophy of Walter Benjamin as reference for conceptual analysis of modern and contemporary cities. The choice by this author is due to the fact that his thinking enables designing the urban centers on the quality of social complex ecosystems, of which depends on the dismissal of most goods and services are essential to the satisfaction of human needs in the world today. Then, it comes to characterize cities as spaces triggers of subtle educational processes, whose effects on the body opens up a series of questions still thirsting for further investigations of part of pedagogies of human movement.